Effects of the Pliensbachian–Toarcian Boundary Event on Carbonate Productivity of a Tethyan Platform and Slope. Issue 5 (19th May 2022) - Fleischmann, Sarah; Picotti, Vincenzo; Caves Rugenstein, Jeremy K.; Cobianchi, Miriam; Bernasconi, Stefano M.
Abstract: We explore the effects of the Pliensbachian–Toarcian Boundary Event (P–ToBE) on tropical carbonate productivity in the interior to margin and slope of the Venetian Platform (Northern Italy). We document the P–ToBE for the first time in the shallow‐water platform margin, and we bio‐ and chemostratigraphically tie it to transgressive/regressive cycles. Following the latest Pliensbachian sea‐level drop and emersion, transgressive grainstones at the platform edge record the P–ToBE negative carbon isotope excursion (CIE) of 1–1.5‰, also found in marl/limestone couplets on the slope. Recovery of platform productivity was ephemeral, as the platform drowned right after the peak negative CIE and was covered by deep‐sea thin‐bedded micritic limestones. The end of the P–ToBE correlates with a regression and renewed recovery of carbonate productivity. The negative CIE of the subsequent Toarcian Oceanic Anoxic Event is recorded in open‐sea cherty limestones both at the marginal and interior platform. These limestones document an even wider transgression and the renewed partial drowning of the platform in the Serpentinus Zone. We investigate the causes of the carbon perturbation at the P–ToBE, using a simple carbon cycle model. The duration and magnitude of the CIE suggest a rapid release of methane in driving the CIE, perhaps related to the preceding sea‐level drop and associated cryosphere perturbation, or to thermogenic alteration of coals near the Karoo‐Ferrar Large Igneous Province (LIP). The extent of the warming and the magnitude of the P–ToBE CIE implies a contribution of volcanogenic carbon dioxide from the Karoo‐Ferrar LIP. Key Points: The Pliensbachian–Toarcian Boundary Event is chemo‐ and lithostratigraphically analyzed in sections of the Venetian carbonate platform We find a negative carbon isotope excursion at the Pliensbachian–Toarcian boundary in slope, and, for the first time, in platform sediments Numerical model of the global carbon cycle points toward low δ 13 C carbon as substantial source of total carbon release during this event